DESIGN AND DEVELOPMENT OF ANDROID-BASED LEARNING MEDIA FOR LEARNING ALGORITHM AND DATA STRUCTURE - Rosyid Ridlo, Al Hakim; Rianti Y., Kisworini; Aditia P., Hamid; Agung, Pangestu; Ariep, Jaenul; Yanuar Zulardiansyah, Arief (2021)
Learning media is part of the learning component, the media is included in the discussion of the overall learning system. The use of media is expected to be a special concern in every learning activity, this is to assist the delivery of learning in supporting the advancement of today's technology-based education world. One of the learning techniques is in the form of algorithms and data structures. Technological advances make learning media usable on Android devices. This study aims to design learning media algorithms and data structures based on Android. The research method uses a waterfall-type system development life cycle (SDLC). The results of the study are learning media algorithms and data structures can be designed for Android devices. The results of system testing using black-box testing provide results as expected.